Erastus, Quaestor of Corinth: The Administrative Rank of ὁ οἰκονόμος τῆς πόλεως (Rom 16.23) in an Achaean Colony - Goodrich, John K. (New Testament studies, 2010)
Erastus (Rom 16.23) has featured prominently in the ongoing debate over the social and economic make-up of the early Pauline communities, since how one renders his title (ὁ οἰκονόμος τῆς πόλεως) dramatically affects the range of economic stratification represented in the Corinthian church. Relying chiefly on epigraphy, including an important new inscription from the Achaean colony of Patras, this article engages the scholarly dialogue about the Latin equivalent of Erastus' title, rebutting the arguments in favour of arcarius and aedilis, and contends that he served as quaestor, a high-ranking municipal position exclusively occupied by the economic elite.